Mechanisms of Epidermal Growth Factor Effect on Animal Intestinal Phosphate Absorption: A Review - Tang, Xiaopeng; Liu, Xuguang; Liu, Hu (Frontiers in Veterinary Science, 2021)
Phosphorus is one of the essential mineral elements of animals, which plays an important role in animal growth and development, bone formation, energy metabolism, nucleic acid synthesis, cell signal transduction and blood acid-base balance. It has established that NaPi-IIb protein is the major sodium-dependent phosphate (Pi) transporter, which plays an important role in Pi uptake across the apical membrane of epithelial cells in the small intestine. Previous studies have demonstrated that epidermal growth factor (EGF) is clearly involved in regulating intestinal Pi absorption. Here we summarized the effects of EGF on active Pi transport mediated by Type IIb sodium dependent phosphate cotransporters (NaPi-IIb) under different conditions, i.e., under normal conditions, EGF inhibited the active transport of Pi by inhibiting the expression of NaPi-IIb, while, under intestinal injury condition, EGF promoted the active absorption of Pi through upregulating the expression of NaPi-IIb. This review could provide a foundation and reference for further investigating about EGF-regulatory functions in Pi absorption in animal intestine.